The Paradigm Shift in Marketing- Case Studies - Jaiswal, K. S.; Singh, Neetu (Indian Journal of Marketing, 2006)
"Paradigm" is set of broadly shared assumption about how to gather and interpret information relevant to a particular sphere of activity. When a group acquires near universal faith in the validity of the system of representing and applying information that system attains paradigmatic standing.Thomas Kuhn in his classic work. The structure of Scientific Revolution, defined the established order, which enjoys a certain predictability, and harmony as "Paradigm" When accepted scientific ideas or principles are invalidated by breakthrough discoveries this is "Paradigm Shift" which is inevitable and predictable in its effect. Paradigm shift is a significant change from one fundamental view to another. It just does not happen, but rather it is driven by agents of change for example, the introduction of the personal computer and the internet have impacted both personal and business environment, and is a catalyst for a paradigm shift.